Microbiota-Derived Phenylacetylglutamine Associates with Overall Mortality and Cardiovascular Disease in Patients with CKD - Poesen, Ruben (J Am Soc Nephrol, 2016)
Colonic microbial metabolism substantially contributes to uremic solute production. p-Cresyl sulfate and indoxyl sulfate are the main representatives of solutes of microbial origin and also, protein-bound solutes, exhibiting high protein-binding affinity and dependence on tubular secretion. Phenylacetylglutamine is another microbial metabolite with high dependence on tubular secretion but low protein-binding affinity. The relevance of such solutes is unknown. Therefore, we prospectively followed 488 patients with CKD stages 1–5 and a measurement of serum phenylacetylglutamine by liquid chromatography-mass spectrometry. In a subgroup, we determined 24-hour urinary excretion as a surrogate of intestinal uptake as well as renal clearance of phenylacetylglutamine. We performed outcome analysis for mortality (51 events) and cardiovascular disease (75 events). Serum phenylacetylglutamine level correlated with 24-hour urinary excretion (rho=0.55; P<0.001) and clearance of phenylacetylglutamine (rho=−0.76; P<0.001). Phenylacetylglutamine clearance also correlated with eGFR (rho=0.84; P<0.001). Furthermore, serum phenylacetylglutamine level associated with mortality (hazard ratio per 1-SD increase, 1.77; 95% confidence interval, 1.22 to 2.57; P=0.003) and cardiovascular disease (hazard ratio, 1.79; 95% confidence interval, 1.32 to 2.41; P<0.001) after adjustment for age, sex, presence of diabetes mellitus, prior cardiovascular disease, and eGFR. Thus, serum phenylacetylglutamine level is elevated in patients with more advanced CKD and determined by intestinal uptake and renal clearance, and it is not fully accounted for by differences in eGFR. High serum phenylacetylglutamine level is a strong and independent risk factor for mortality and cardiovascular disease, suggesting the relevance of microbial metabolism and/or tubular dysfunction in CKD, irrespective of protein binding.